2018
DOI: 10.1002/ece3.4639
|View full text |Cite|
|
Sign up to set email alerts
|

Effect of temperature on the biological parameters of the cabbage aphid Brevicoryne brassicae

Abstract: The cabbage aphid, Brevicoryne brassicae, is a pest of many plants of the Brassicaceae family including cabbage, Brassica oleracea Linnaeus, 1753. We investigated the effect of temperature on the biological parameters of B. brassicae using different temperature‐based models incorporated in the Insect Life Cycle Modelling (ILCYM) software. Nymphs of first stage were individually placed in the incubators successively set at 10°C, 15°C, 20°C, 25°C, 30°C, and 35°C; 75 ± 5% RH; and L12: D12‐hr photoperiods. We foun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 53 publications
4
13
0
Order By: Relevance
“…These findings are in agreement with that of previous studies by Bowling [62], who worked with Acheta domesticus and proof that a shift from 29.4°C to 35°C had a huge impact on the nymphal developmental duration, which decreased by 28 days. The lower development thresholds described by the linear model is in line with that for other insect species [1718, 36, 6365]. At the optimal temperature threshold, S .…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…These findings are in agreement with that of previous studies by Bowling [62], who worked with Acheta domesticus and proof that a shift from 29.4°C to 35°C had a huge impact on the nymphal developmental duration, which decreased by 28 days. The lower development thresholds described by the linear model is in line with that for other insect species [1718, 36, 6365]. At the optimal temperature threshold, S .…”
Section: Discussionsupporting
confidence: 80%
“…At the optimal temperature threshold, S . icipe had the highest survival rate accompanied by short generation time, which are considered as important criteria for mass production [6566]. According to Patton [67], life table studies obtained under constant temperatures provide useful information on the biology and ecology of insects, which explain the dynamics that might occur within and between S .…”
Section: Discussionmentioning
confidence: 99%
“…Similar results have been reported for Rhopalosiphum padi [35,37,38] and Tuberolachnus salignus [39]. The lengths of the immature stages of other aphid species, such as Nasonovia ribisnigri [40], Aphis punicae [41], Schizaphis graminum [42], Aphis fabae [26], Aphis craccivora [43] and Brevicoryne brassicae [44], decreased up to~25 • C and increased above 25 • C. Total longevity also declined as temperature increased from 10 • C to 30 • C, as has also been observed for A. fabae, R. padi, A. craccivora and B. brassicae. The age-specific survival rate (l x ) curves sharply dropped at earlier ages when the temperatures ranged from 20 • C to 30 • C. Several studies have also shown the detrimental effects of higher temperatures on the survivorship of various aphid species, such as R. padi, Toxoptera aurantii, A. fabae, A. craccivora, Sitobion avenae and Metopolophium dirthodum [45,46].…”
Section: Discussionsupporting
confidence: 77%
“…Similar results have been reported for Rhopalosiphum padi [ 35 , 37 , 38 ] and Tuberolachnus salignus [ 39 ]. The lengths of the immature stages of other aphid species, such as Nasonovia ribisnigri [ 40 ], Aphis punicae [ 41 ], Schizaphis graminum [ 42 ], Aphis fabae [ 26 ], Aphis craccivora [ 43 ] and Brevicoryne brassicae [ 44 ], decreased up to ~25 °C and increased above 25 °C. Total longevity also declined as temperature increased from 10 °C to 30°C, as has also been observed for A. fabae , R. padi , A. craccivora and B. brassicae .…”
Section: Discussionmentioning
confidence: 99%
“…The number of eggs laid per female increased from 7.00 at 27˚C to 164.86 at 30˚C. Soh et al (2018) 325.12 < 0.000 n = effective replicate number;X = mean value; SE = standard error; F = F value of Tukey's Test; P = statistical significance. Means ± SE followed by different letters in the same row are significantly different at P < 0.…”
Section: Resultsmentioning
confidence: 99%